2020
DOI: 10.21203/rs.3.rs-62412/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of dietary licorice extract on serum Biochemical index, tissues antioxidant capacity and immunity function of weaned piglets

Abstract: Background: This study investigated the effects of dietary licorice extract (LE) on antioxidant capacity and immunity in weaned piglets. A total of 96 DLY (Duroc × Landrace × Yorkshire) weaned piglets were randomly assigned to four treatments. The control group were fed a corn–soybean meal-based diet (basal diet, BD), and three LE level groups were fed on BD supplied with 50、150 and 250 mg/kg LE. The trial lasted 5 weeks. At day 35, six piglets per treatment were killed and blood, liver, spleen, and thymus wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Similarly, supplementation of dandelion leaf powder increased the concentration of serum GSH-Px but decreased the concentration of MDA in broilers ( 59 ). Licorice extract, as the other ingredient in the mixture of herbal medicine, increased serum T-AOC level, and 50 mg/kg increased serum T-SOD activity and decreased serum MDA concentration in weaned pigs ( 60 ). It had been reported that paeoniflorin inhibits cell apoptosis, improves cell viability, and increases the concentration of SOD and CAT ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, supplementation of dandelion leaf powder increased the concentration of serum GSH-Px but decreased the concentration of MDA in broilers ( 59 ). Licorice extract, as the other ingredient in the mixture of herbal medicine, increased serum T-AOC level, and 50 mg/kg increased serum T-SOD activity and decreased serum MDA concentration in weaned pigs ( 60 ). It had been reported that paeoniflorin inhibits cell apoptosis, improves cell viability, and increases the concentration of SOD and CAT ( 61 ).…”
Section: Discussionmentioning
confidence: 99%